Τ-Complexity and Tilting Modules. (7th June 2016) - Zheng, Lijing; Huang, Chonghui; Wan, Qianhong
Abstract : LetA be a finite dimensional algebra over an algebraic closed fieldk . In this note, we will show that ifT is a separating and splitting tiltingA -module, thenτ -complexities ofA andB are equal, whereB = End A ( T ) .